The conceptualisation principles of an academic literacy course: an interpretive study of the English for academic purposes module at a Namibian University - Onomo, Angelina Medzo (Rhodes University, Faculty of Education, Department of Education, 2018)
This thesis reports on an investigation into the features of an English for Academic Purposes (EAP) course that may promote or constrain students' success at the Namibia University of Science and Technology (NUST). Work by the New Literacy Studies has problematised what it means to be academically literate and has critiqued the notion of skills training in Higher Education. This study sought to develop an understanding of what the coursework writers' and lecturers' priorities were in designing and assessing academic literacy as expressed in the English for Academic Purposes (EAP) module, and to explain contradictions. As part of this process, it sought to identify the module's strengths and weaknesses in terms of an understanding of literacy as a social practice, and to recommend changes if necessary. My interest in this module is a result of two interrelated factors. Firstly, as a novice part-time lecturer at NUST, I became concerned at the prevailing high EAP failure rate, which suggested that the course was not in fact promoting the academic literacy of the students. At the same time, my own attempts at 'equipping' students with the required academic literacy skills were frustrating. Both these factors suggested that the design and assessment of the course might be misaligned with its purported aims. To carry out this research, I employed an interpretive paradigm using a qualitative approach. I draw on theories in the field of academic literacies by Gee, Street and Lea. The methodology for the study was a document analysis of coursework materials and assessments, supplemented by interviews with available course designers. The key finding of the research is that the aims of the module are undercut by its structure and presentation. The design and assessment tasks of this module, while they aim at giving epistemological access through the development of students' academic literacy skills, are unlikely to achieve it. This finding explains to some extent the poor throughput rate of the course.
Keywords: Academic writing -- Study and teaching -- Namibia; Information literacy -- Study and teaching -- Namibia; Information literacy -- Social aspects -- Namibia; Academic language -- Namibia; Qualitative research -- Methodology